Cytomegalovirus-associated renal allograft rejection: new challenges for antiviral preventive strategies - Reischig, Tomás (Expert review of anti-infective therapy, 2010)
The adverse impact of cytomegalovirus (CMV) infection after solid organ transplantion is currently believed to be mediated primarily by its immunomodulatory effects. There is a large body of evidence showing that both CMV disease and asymptomatic viremia are independent risk factors for the development of allograft rejection. The aim of this article is to summarize mechanisms whereby CMV is involved in the development and progression of allograft rejection, with particular emphasis on renal transplant recipients. The article will also address the potential of anti-CMV preventive protocols designed to favorably affect the incidence of allograft rejection.
Keywords: rejekce štěpu; Chemoprevention; cytomegalovirové infekce; Kidney Transplantation; antivirové látky; homologní transplantace; Cytomegalovirus; Humans; Antiviral Agents; Cytomegalovirus Infections; lidé; Graft Rejection; transplantace ledvin; chemoprofylaxe; Transplantation, Homologous